PEMBINAAN PESERTA DIDIK DALAM IMPLEMENTASI KEBIJAKAN SISTEM ZONASI DI SMAN 1 SRENGAT - Chusnul Chotimah; Ahmad Kholil (LP2M IAIN Tulungagung, 2021)
New Student Admission, hereinafter abbreviated as PPDB, is stated in the Regulation of the Minister of Education and Culture of the Republic of Indonesia Number 51 of 2018, carried out based on the principles of non-discrimination, objective, transparent, accountable and fair. One of them is implemented with the PPDB zoning system policy. The New Student Admission (PPDB) zoning system raises a number of impacts. In practice, SMAN 1 Srengat has encountered several effects that have arisen since the implementation of the PPDB zoning system. Among them are the random input of students and the low enthusiasm for learning in students who are accepted through the zoning route without any selection with qualifications based on the acquisition of learning outcomes at the previous level. This research tries to review overcoming the problems of the teaching and learning process after the implementation of the zoning system PPDB policy at SMAN 1 Srengat. So that it can be seen that, in response to the implementation of the PPDB policy of the zoning system which generates random input and raises problems in the spirit of learning, SMAN 1 Srengat implements innovation and development of transformative and comprehensive student coaching.